(untitled) (Contemporary Journal of Social Science Review, 2025)
Successful implementation of change has become more important than ever if firms, particularly in the technology industry, are going to survive in today’s uncertain business environment. Organizational readiness to change has been identified as a significant antecedent to successful change, but little attention has been paid to how it interacts with important end results such as project performance and rates of adoption. The primary purpose of this paper is to examine the extent to which both organizational commitment and project performance mediate the relationship between organizational readiness to change and the self-reported success of firms in implementing change, as measured by their rates of adoption of change. Data were obtained via a cross-sectional survey of 248 project managers and project team members involved in technology companies, especially in US based information technology (IT) firms. The hypothesized model was tested by using partial least squares structural equation modeling (PLS SEM). The results indicate that organizational readiness to change has a significantly positive direct effect on both project performance (β = .38, p < .0001) and rate of adoption of institutional change (β = .29, p < .0001). Although there may also be direct effects of both workgroup and organizational commitment on these latter two variables in the hypothesized model, this study indicates that they are important mediating variables as well since there are significant indirect effects (β = .18, p < .01 for change rate; β = .15, p < .01 for project performance). It appears then that the impact of organizational readiness to change is indeed a very significant determinant of the success of change initiatives, both through direct effects and indirect ones, namely in that they lead to the creation of an environment where work force commitment is present. This study makes a contribution to the field of change management theory in that it identifies a psychological antecedent to change success, namely that of organizational commitment, as a mediating variable in the hypothesized relationship between organizational readiness to change and both project performance and rate of adoption. For organizational practitioners, this research study points out both the importance of organizational readiness to change and the need for organizational commitment in any efforts at facilitating organizational change, if the chances for success of change efforts are to increase.